Perlindungan Hukum Bagi Korban Kekerasan Seksual dalam Penerapan Diversi dengan Pendekatan Keadilan Restoratif dalam Sistem Peradilan Anak - Batubara, Hirsan; Nurhayati, Nurhayati; Zuliah, Azmiati (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the legal protection of victims of sexual violence in the application of diversion based on restorative justice within Indonesia’s juvenile justice system. The research is grounded in the gap between the ideal concept of restorative justice, which upholds restorative values, and its practical implementation that often neglects the rights of victims, particularly children who experience sexual violence. This situation creates a dilemma between the principle of protecting juvenile offenders and ensuring substantive justice for victims. The study employs a normative juridical method with statutory, conceptual, and analytical approaches through a literature review of primary, secondary, and tertiary legal materials. The findings reveal that the implementation of restorative justice in cases of child sexual violence faces several obstacles, including the ambiguity of diversion limits, the absence of specific standard operating procedures, and the lack of involvement of psychologists and social workers representing victims’ interests. Theoretically, this study contributes to strengthening the victim-oriented perspective within Indonesia’s restorative justice framework, which has been predominantly offender-centered. Practically, it recommends the formulation of more assertive and comprehensive legal policies to ensure a balance between the rehabilitation of offenders and the restoration of victims’ rights, including the establishment of specific SOPs and monitoring mechanisms for diversion implementation. Thus, this research addresses the existing gap in the practice of restorative justice by asserting that true justice can only be achieved when the juvenile justice system equally prioritizes the protection and recovery of victims.